PERANCANGAN VISUAL BRANDING KLINIK KECANTIKAN MELALUI KONTEN KOLABORASI INFLUENCER (STUDI KASUS: EDERMA CLINIC SEMARANG) - Riezka Safina Putri; Irdha Yunianto (Pixel :Jurnal Ilmiah Komputer Grafis, 2025)
This study discusses the design of visual branding for Ederma Clinic Semarang through influencer collaboration content. The researcher acts as the influencer to produce creative visual content that represents Ederma Clinic’s identity, increases engagement, and strengthens brand awareness among young women audiences. The research method used is qualitative descriptive with data collection through observation, interviews, documentation, and content analysis. The results show that influencer collaboration can improve brand perception, social media engagement, and customer interest in Ederma Clinic. The designed visual content successfully strengthens brand positioning as a trusted and modern beauty clinic.